2022
DOI: 10.1109/jstars.2022.3216463
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Freezing and Thawing Surface State Periods With the CYGNSS Based F/T Seasonal Threshold Algorithm

Abstract: Freeze/Thaw (F/T) surface state detection and imaging has been demonstrated as a capability of NASA's Cyclone Global Navigation Satellite System (CYGNSS) mission. The objective of the research presented here is the application of an existing F/T retrieval algorithm to multiple target areas over several years in order to demonstrate the ability to provide long term trending of F/T behavior. Metrics are developed and evaluated to characterize F/T trends related to global warming. They include the annual fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It is the first GNSS-R pathfinder mission consisting of eight Low Earth Orbiting (LEO) micro-satellites. CYGNSS was launched in December 2016 with the main objective of near-surface ocean wind and currents monitoring (e.g., [34], [35], [36]); however, it can also be used as tool for the remote sensing of other environmental features, including but not limited to, inland water monitoring (e.g., [37], [38], [39]), soil moisture, wetlands and biomass observation ( [40], [41], [42]), freeze/thaw state retrieval ( [43], [44]), and mesoscale ocean eddies observations [45]. Mayer and Ruf [46] proposed the potential of CYGNSS for conducting altimetry over lake ice and using the transparency of ice to GNSS L-band signals to infer ice thickness.…”
Section: > Replace This Line With Your Manuscript Id Number (Double-c...mentioning
confidence: 99%
“…It is the first GNSS-R pathfinder mission consisting of eight Low Earth Orbiting (LEO) micro-satellites. CYGNSS was launched in December 2016 with the main objective of near-surface ocean wind and currents monitoring (e.g., [34], [35], [36]); however, it can also be used as tool for the remote sensing of other environmental features, including but not limited to, inland water monitoring (e.g., [37], [38], [39]), soil moisture, wetlands and biomass observation ( [40], [41], [42]), freeze/thaw state retrieval ( [43], [44]), and mesoscale ocean eddies observations [45]. Mayer and Ruf [46] proposed the potential of CYGNSS for conducting altimetry over lake ice and using the transparency of ice to GNSS L-band signals to infer ice thickness.…”
Section: > Replace This Line With Your Manuscript Id Number (Double-c...mentioning
confidence: 99%
“…It is shown that the combined waveform is with a steeper leading edge slope (LES). According to (26), the ranging standard deviation (STD) is partly determined by the ranging sensitivity S r , which is defined as the normalized slope of the waveform. Therefore, the increasing LES of the combined waveform will contribute to increasing S r and reducing the ranging STD, which implies better altimetry performance.…”
Section: Combination Of Reflected Waveformsmentioning
confidence: 99%
“…As calculated in Section III-C2, the combined waveform exhibits an improved SNR. According to (26), both the altimetry sensitivity S r and SNR of the combined waveform increase. Hence, the theoretical range precision σ ρ should be improved.…”
Section: Preliminary Performance Validation In Geophysical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…NASA launched the Cyclone Global Navigation Satellite System (CYGNSS) in 2016, which comprises eight microsatellites. The scientific applications of this constellation have expanded beyond the detection of ocean parameters to include monitoring and retrieval of soil moisture, vegetation biomass, flood inundation, wetlands, and near-surface soil freeze/thaw state [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is worth noting that the two GNSS-R CubeSats recently launched by Spire also have the capability to provide soil moisture products [22].…”
Section: Introductionmentioning
confidence: 99%